Process Development and Optimization of New Analogues of Isatin - SWAPNA VADLAMANI; VIDYA SRILEKHA (International Journal of Pharma and Bio Sciences, 2018)
Isatin and its derivatives possess broader range of biological activity. High bilogical activity and potency of Isatins Motivated our current work which involves synthesis of novel analogues of this natural product. Initial screening of the analogues by molecuar docking studies was carried out by using schordinger software. Best analogues with good glide score and interactions were selected and were synthesized.Optimization studies were carried our for the analogues.Charecterization of the analogues was done using LC-MS and NMR studies and included in the supporting information.